(3GdTGaj aj GdLhGH Ydi GdQSGdI GdNGQbI dCHf CHj GdbHGFd YHO GdQMef Hf efUhQs - (3CHh eMeO YHO Gddg Hf MeRI Hf SdjeGf Hf MeRI GdMSfj Gdjefj,J (B614 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi bUQ Yf JCOjI eG jMH dg ef GdMb MeO GdMGeOjf , hdG Edg EdG Gddg EQZekG dEfha GdLGMOjf s
(3BNQgG (B:s
(3BNQg eHJhQ hChd GdehLhO efg (B: (3bUjOI GdgjKe Hf YHO Gddg GdNKYei GdJi jSJgdgG Hbhdg (B: (3SGFd Yf GdXGYfjf eG aYdhG hCjf HYO EQJMGdge fRdhG s
(3GdLRA GdChd ef fSNI KGdKI hgj GdQSGdI GdJi HYK HgG GHf CHj GdbHGFd Edi GdEeGe GdePchQ ai TgQ ThGd SfI (B608 (3g`s
(3GdfSNI HgG MhGTs
(3cJHJ HYV GdYfhGfGJ HGdMeQI Ch HCdhGf CNQi s
(3Ydi MhGTjgG ebGHdGJ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B83s
Keywords: (3abg GdePGgH GdCNQis